Carrier Doping Physics of Rare Earth Perovskite Nickelates RENiO3 - Li, Jiarui; Ramanathan, Shriram; Comin, Riccardo (Frontiers in Physics, 2022)
The family of rare earth (RE) nickelate perovskites RENiO3 has emerged over the past two decades as an important platform for quantum matter physics and advanced applications. The parent compounds from this family are strongly correlated insulators or metals, in most cases with long-range spin order. In the past few years, carrier doping has been achieved using different approaches and has been proven to be a powerful tuning parameter for the microscopic properties and collective macroscopic states in RENiO3 compounds. In particular, a series of recent studies has shown that carrier doping can be responsible for dramatic but reversible changes in the long-range electronic and magnetic properties, underscoring the potential for use of nickelates in advanced functional devices. In this review, we discuss the recent advancements in our description, understanding and application of electron-doped rare earth nickelates. We conclude with a discussion of the developments and outlook for harnessing the quantum functional properties of nickelates in novel devices for sensing and neuromorphic computation.